Economic growth without structural transformation: The case of Ethiopia - Dorosh, Paul A.; Schmidt, Emily; Shiferaw, Admasu (Pennsylvania State University Press, 2012)
Ethiopia is a highly agrarian economy, with a long history of substantial food insecurity. In recent years, however, the economy has seen substantial economic transformation, largely in the form of increased agricultural productivity and significant improvements in road infrastructure. But while these investments have contributed to impressive poverty reduction in recent years, structural transformation has been inhibited by the relatively slow development of an industrial sector, and modest rates of urbanization. Future development strategies will therefore need to search for the right balance between pro-poor investments in agriculture and rural development, and potentially more transformative investments in urban infrastructure and industry.